Interaksi Sosial dan Konsep Diri dengan Kecanduan Games Online pada Dewasa Awal - Ayu, Lestari; Saragih, Sahat (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
This study aims to determine: 1) the relationship between social interaction and self-concept in online gaming addiction in early adulthood; 2) The contribution of social interaction for online gaming addiction; 3) contribution up to the concept of online gaming addiction. The hypothesis put forward: there is a negative relationship between social interaction and self-concept in online gaming addiction. Subjects were young adult males aged 18-40 years, who love to play online games (PC games or games HP). The process of selecting a subject taken by purposive sampling. Data were analyzed by regression analysis. Before performing regression analysis, first necessary to test the assumption of research data. Test assumptions made in this study included tests of normality and linearity test. The results showed that there is a relationship between social interaction and self-concept in online gaming addiction.Keywords : social interaction, self-concept, online gaming, online gaming addiction